Analysis of CO2 emission reduction contribution and efficiency of China's solar photovoltaic industry: Based on Input-output perspective. (15th May 2020) - Ren, Fang-rong; Tian, Ze; Liu, Jingjing; Shen, Yu-ting
Abstract: As one of the most promising renewable energy sources, the amount of solar photovoltaics has reached 104.1 GW in 2018. China not only has the natural advantages of abundant solar energy resources, but the photovoltaic industry under the government's support has also become the main driving force for global development. Facing the structural adjustment of solar photovoltaic parity online and the important contribution of solar power generation to energy conservation and emission reduction, this paper based on the radial and non-radial comprehensive consideration of EBM (Epsilon-Based Measure) DEA (Data envelopment analysis) model from the input-output perspective on solar photovoltaic industry CO2 emission reduction and efficiency analyze. It is concluded that the total efficiency of the solar photovoltaic industry in China's six regions shows a growing trend, but the regional differences are obvious. The overall efficiency of the northwest region is superior. Among the index efficiency, CO2 emission reduction efficiency is better than cumulative installed capacity efficiency, solar energy utilization hour efficiency is the lowest, and CO2 emission reduction and cumulative installed capacity efficiency all show a consistent trend. It shows that the efficiency of cumulative installed capacity has a positive impact on CO2 emission reduction, but the efficiency of solar power generation needs to be improved. Highlights: Evaluating the efficiency of china's solar photovoltaic industry from the input-output perspective. Using the EBM model based on linear and nonlinear factors. Discussing the contribution of China's solar photovoltaic industry to CO2 emission reduction. The efficiency of cumulative installed capacity has positive impact on CO2 emission reduction, but need to be improved.